2023
DOI: 10.3390/cimb45040222
|View full text |Cite
|
Sign up to set email alerts
|

AKR1B1 Represses Glioma Cell Proliferation through p38 MAPK-Mediated Bcl-2/BAX/Caspase-3 Apoptotic Signaling Pathways

Abstract: This study aimed to investigate the regulatory role of Aldo-keto reductase family 1 member B1 (AKR1B1) in glioma cell proliferation through p38 MAPK activation to control Bcl-2/BAX/caspase-3 apoptosis signaling. AKR1B1 expression was quantified in normal human astrocytes, glioblastoma multiforme (GBM) cell lines, and normal tissues by using quantitative real-time polymerase chain reaction. The effects of AKR1B1 overexpression or knockdown and those of AKR1B1-induced p38 MAPK phosphorylation and a p38 MAPK inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Based on their roles, members of the Bcl-2 family can be divided into three groups: pro-apoptotic proteins Bax, pro-apoptotic activators like NOXA and PUMA, and anti-apoptotic proteins Bcl-2 [43,44]. Bcl-2 binds to Bax and interacts to prevent mitochondrial pore formation, thereby inhibiting the execution of cell apoptosis [45,46]. In this study, we found that PEDV infection can promote the expression of p53 in IPEC-J2 cells at 18 h post-infection.…”
Section: Discussionmentioning
confidence: 99%
“…Based on their roles, members of the Bcl-2 family can be divided into three groups: pro-apoptotic proteins Bax, pro-apoptotic activators like NOXA and PUMA, and anti-apoptotic proteins Bcl-2 [43,44]. Bcl-2 binds to Bax and interacts to prevent mitochondrial pore formation, thereby inhibiting the execution of cell apoptosis [45,46]. In this study, we found that PEDV infection can promote the expression of p53 in IPEC-J2 cells at 18 h post-infection.…”
Section: Discussionmentioning
confidence: 99%
“…p38 MAPK is activated in response to various stress signals, including DNA damage, oxidative stress, and cytokines. Once activated, p38 MAPK can induce cell cycle arrest ( Faust et al, 2012 ) or apoptosis ( Huang et al, 2023 ), effectively eliminating potentially cancerous cells. Furthermore, p38 MAPK signaling initiates G1 mitotic arrest not only in cancer cells but also in a variety of terminally differentiated cell types ( Perdiguero et al, 2007 ; Molnár et al, 1997 ; Xiu et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-x, a member of the Bcl-2 family, and Bax proteins regulate the survival and apoptosis of mouse PGCs during embryogenesis ( Rucker et al, 2000 ), and a subpopulation of migrating PGCs are positive for phosphorylated p38 MAPK protein ( Figure 1E ). As p38 MAPK-induced BAX/Bcl-2/caspase-3 apoptosis signaling is involved in glioma cell proliferation ( Huang et al, 2023 ), p38 MAPK may play a pivotal role in controlling PGCs output by eliminating damaged or unscheduled pluripotency expression through mediation with Bcl-x and Bax proteins. In considering another potential role of p38 MAPK in reprogramming, it is noteworthy that the PI3K-Akt signaling pathway is highly activated in cEGLCs and that they are more strongly dependent on its signaling than conventional EGCs in maintaining undifferentiated state ( Figures 4B,C ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, P38 MAPK pathway has been evidenced to mediate apoptosis [43]. Studies have shown that phosphorylated P38 MAPK can activate caspase-3 and promote apoptosis by downregulating Bcl-2 [44][45][46]. Thereby, VK2 reduced lung cell apoptosis by inhibiting LPS-induced activation of P38 MAPK.…”
Section: Discussionmentioning
confidence: 99%